Pengaruh Pelayanan ATM BNI Terhadap Tingkat Kepuasan Nasabah : Studi Kasus di BNI Cabang Tasikmalaya - Ading Rahman Sukmara; Aga Yogasara; Ferey Herman (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
The problems faced in this study include (1) How does BNI ATM service influence in terms of direct evidence (tangibles) on the level of customer satisfaction at BNI Tasikmalaya Branch? (2) How does BNI ATM service influence in terms of reliability on the level of customer satisfaction at BNI Tasikmalaya Branch? (3) How does BNI ATM service influence in terms of responsiveness on the level of customer satisfaction at BNI Tasikmalaya Branch? (4) How does BNI ATM service influence in terms of assurance on the level of customer satisfaction at BNI Tasikmalaya Branch? (5) How does BNI ATM service influence in terms of empathy on the level of customer satisfaction at BNI Tasikmalaya Branch? (6) How does BNI ATM service influence which consists of direct evidence (tangibles), reliability, responsiveness, assurance, and empathy on the level of customer satisfaction at BNI Tasikmalaya Branch? The purpose of this study was to study, determine, and analyze the influence of ATM services (tangibles, reliability, responsiveness, assurance, and empathy) on the level of customer satisfaction at BNI Tasikmalaya Branch. The method used in this study was an explanatory survey, while the technical data analysis was validity testing, reliability testing, descriptive statistics, Inductive Statistical Analysis with Multiple Regression. The results of the study inform that (1) Tangibles have a positive effect on the level of customer satisfaction at BNI Tasikmalaya Branch. This means that if tangibles are increased, the level of customer satisfaction will also increase. (2) Reliability has a positive effect on the level of customer satisfaction at BNI Tasikmalaya Branch. This means that if reliability is increased, the level of customer satisfaction will also increase. (3) Responsiveness has a positive effect on the level of customer satisfaction at BNI Tasikmalaya Branch. This means that if responsiveness is increased, the level of customer satisfaction will also increase. (4) Assurance has a positive effect on the level of customer satisfaction at BNI Tasikmalaya Branch. This means that if direct evidence (tangibles), reliability, responsiveness, assurance and empathy are increased, then the level of customer satisfaction will also increase. (5) Empathy has a positive effect on the level of customer satisfaction at BNI Tasikmalaya Branch. This means that if empathy is increased, then the level of customer satisfaction will also increase. (6) Direct evidence (tangibles), reliability, responsiveness, assurance and empathy have a positive effect on the level of customer satisfaction at BNI Tasikmalaya Branch. This means that if direct evidence (tangibles), reliability, responsiveness, assurance and empathy are increased, then the level of customer satisfaction will also increase.